2019
DOI: 10.1109/tcbb.2019.2910814
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Markov Modelling Reveals Neighborhood Dependence of Dnmt3a and 3b Activity

Abstract: DNA methylation is an epigenetic mark whose important role in development has been widely recognized. This epigenetic modification results in heritable information not encoded by the DNA sequence. The underlying mechanisms controlling DNA methylation are only partly understood. Several mechanistic models of enzyme activities responsible for DNA methylation have been proposed. Here, we extend existing Hidden Markov Models (HMMs) for DNA methylation by describing the occurrence of spatial methylation patterns ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Data from ESCs with Dnmt3a/b DKO, for instance, gives ψ L ≈ ψ R ≈ 1 when fitted to this model because maintenance through Dnmt1 occurs independent of the state of neighboring CpGs. In contrast, calibration of the model to Dnmt1 KO data shows a clear dependence of the methylation activity of Dnmt3a/b to the left [17].…”
Section: Modelmentioning
confidence: 77%
See 3 more Smart Citations
“…Data from ESCs with Dnmt3a/b DKO, for instance, gives ψ L ≈ ψ R ≈ 1 when fitted to this model because maintenance through Dnmt1 occurs independent of the state of neighboring CpGs. In contrast, calibration of the model to Dnmt1 KO data shows a clear dependence of the methylation activity of Dnmt3a/b to the left [17].…”
Section: Modelmentioning
confidence: 77%
“…We focus on Dnmt1 KO data, i.e. only Dnmt 3a/b is active, since previous findings suggest, that in general only Dnmt 3a/b shows a dependence on the left neighbor, while Dnmt1 acts independent of the neighborhood [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, DNMT1, a most abundant isoform in proliferating cells, could maintain the methyltransferase and copy methylation targets with replication forks during replication at sites of DNA repair. DNMT3a and DNMT3b methylate specific DNA targets in response to environmental factors [22,23]. It has been observed that persistent pain can alter expression of DNMTs.…”
Section: Discussionmentioning
confidence: 99%